Measuring economic diplomacy using event study method: the case of EU-China summit talks and Airbus stock price changes. - Choi, Sunkung (Asia Europe Journal, 2023)
Economic diplomacy receives growing interest in the field of international relations research ever since the end of the cold war. Despite the vast number of literature on economic diplomacy, there are not many studies measuring the effect of economic diplomacy quantitatively. The purpose of this paper is to propose a method to measure economic diplomacy using the event study method that observes the influence of specific events on stock prices. In this study, the summit talks between the EU and China are selected as specific events that are considered as a form of economic diplomacy, and Airbus stock price, the proxy of the reaction to the economic diplomacy, was observed to verify the influence of it. The study categorized the summit talks by the type of participants whether the top politicians were included or not. The result shows that, among all summit talks, the summit talks between top politicians between the EU and China influence the stock price of Airbus positively, and it is statistically significant.